Adaptive communication strategies for sustaining public political participation: Lessons from the 2024 Surakarta regional election - Djayanti Poetria Handayaningsih; Rahmat Wisudawanto; Dyah Retno Pratiwi (Societa: Journal of Society and Change, 2026)
Communication strategies implemented by election management bodies play a crucial role in sustaining voter participation. However, previous studies have primarily focused on voter outreach activities or the utilization of digital media without integrating the entire communication strategy process with SWOT analysis. This study aims to analyze the communication strategy of the General Election Commission (Komisi Pemilihan Umum [KPU]) of Surakarta City in sustaining voter participation during the 2024 Regional Head Election. A descriptive qualitative approach was employed using interviews, observations, and document analysis, with the data analyzed through the interactive model. The findings indicate that the communication strategy was implemented through the stages of research, planning, execution, measurement, and reporting, supported by systematic planning, multi-stakeholder collaboration, and the effective use of digital media. Nevertheless, its implementation continues to face challenges related to low social media engagement, disparities in digital literacy, and the spread of disinformation. The SWOT analysis demonstrates that sustaining voter participation depends on the organization's ability to adaptively integrate internal strengths with external opportunities. This study contributes to the literature on election communication strategies by integrating the stages of communication strategy with SWOT analysis. Abstrak Strategi komunikasi penyelenggara pemilu berperan penting dalam mempertahankan partisipasi pemilih. Namun, penelitian sebelumnya umumnya berfokus pada pelaksanaan sosialisasi atau pemanfaatan media digital tanpa mengintegrasikan keseluruhan tahapan strategi komunikasi dengan analisis SWOT. Penelitian ini bertujuan menganalisis strategi komunikasi Komisi Pemilihan Umum (KPU) Kota Surakarta dalam mempertahankan partisipasi pemilih pada Pilkada Tahun 2024. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui wawancara, observasi, dan studi dokumentasi. Data dianalisis menggunakan model analisis interaktif. Hasil penelitian menunjukkan bahwa strategi komunikasi diimplementasikan melalui tahapan research, planning, execution, measurement, dan reporting yang didukung oleh perencanaan yang sistematis, kolaborasi multipihak, serta pemanfaatan media digital. Meskipun demikian, implementasinya masih menghadapi berbagai tantangan, seperti rendahnya tingkat keterlibatan pada media sosial, kesenjangan literasi digital, dan penyebaran disinformasi. Analisis SWOT menunjukkan bahwa keberhasilan mempertahankan partisipasi pemilih bergantung pada kemampuan organisasi mengintegrasikan kekuatan internal dengan peluang eksternal secara adaptif. Penelitian ini memberikan kontribusi terhadap pengembangan kajian strategi komunikasi pemilu melalui integrasi tahapan strategi komunikasi dengan analisis SWOT.